Sadari Penyakit Kardiovaskular Sejak Dini Melalui Pemeriksaan Trigliserida Pada Populasi Lansia Di Panti Werdha Hana - Yonathan Adi Purnomo; Alexander Halim Santoso; Farell Christian Gunaidi; Fiona Valencia Setiawan; Bryan Anna Wijaya (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Hypertriglyceridemia is a metabolic condition that often occurs in the elderly and contributes greatly to an increased risk of cardiovascular diseases such as stroke, heart attack, and acute pancreatitis. This condition often does not show symptoms in the early stages, so regular triglyceride level checks are an important step for early detection. The Community Service Program (PKM) at Panti Werdha Hana aims to increase awareness of the elderly about the importance of early detection of dyslipidemia through blood triglyceride level screening activities. This activity uses the Plan-Do-Check-Act (PDCA) approach which includes lipid profile examination and educational counseling on risk factors and prevention of hypertriglyceridemia. Of the 76 elderly participants, it was found that 33 people (43.42%) had high triglyceride levels, while 43 people (56.58%) showed normal levels. These results emphasize the importance of routine checks and education to reduce the risk of cardiometabolic disease and support a healthier and more independent quality of life for the elderly.